Effectiveness of The Implementation Game-Based-Learning in Increasing Student Learning Outcomes - Nabila Nur Maulida; Sukadi Sukadi; Sri Rahayu (Universitas Pendidikan Indonesia, 2022)
The government has now started to lower the Implementation of Community Activity Restrictions level during the Covid-19 pandemic, but it cannot be predicted that it will return to normal. This makes the world of education to be able to choose a learning model whose implementation is flexible both offline and online. Learning outcomes are an indication of the success of a learning process. In line with the previous explanation, the purpose of this study is to determine the effectiveness of implementing Game-Based-Learning (GBL) learning-assisted Kahoot! with digital media in improving student learning outcomes in the subject of Construction Cost Estimation. This research is a pre-experimental design in the form of a one-group pretest-posttest research design. The results of the study show that the application of GBL produces an average score that is more effective than before the treatment, where the value obtained has exceeded the category of determining the completeness of learning outcomes for productive subjects that have been determined. To see the picture that GBL can improve student learning outcomes, it can be seen from the results of the test that the increase in N-Gain has increased with a moderate category. Based on the research findings and discussion in terms of the process and improvement of student learning outcomes, the N-Gain Score of 65.00% is categorized as quite effective, so the application of GBL can be applied according to current conditions and can be more optimal.Keywords: Construction Cost Estimation, Game-Based-Learning (GBL), Kahoot!, Learning Outcomes